Structural and functional units of parenchyma of lymph nodes of dromedaries (Camelus dromedarius) - P. N. Gavrilin; O. G. Gavrilina; V. V. Brygadyrenko; D. E. Rahmoun (Regulatory Mechanisms in Biosystems, 2017)
This article analyzes patterns of structural and functional organization of the parenchyma of different groups of lymph nodes, structural features of their connective tissue frame and lymphatic sinuses. We studied superficial and deep somatic (Limphonodi mandibulares, L. cervicales superficiales, L. axillares proprii, L. poplitei), somatovisceral (L. retropharyngei mediales, L. iliaci mediales), visceral (L. mediastinales caudales, L. jejunales) features of mature male dromedaries (Camelus dromedarius Linnaeus, 1758). We used a complex of traditional macroscopic and histological techniques, and also immunohistochemical staining of lymph node sections for identifying the features of localization of T- and B-lymphocyte populations in the parenchyma of the nodes. We found that the parenchyma of camels’ lymph nodes is characterized by a spongy type structure in the form of a complex of partly concrescent round-oval fragments of lymphoid tissue, surrounded by large lymphatic spaces (sinuses). The connective tissue frame of the lymph nodes is represented by a two-layer (connective tissue-muscular) capsule and two types of trabeculae: two-layered (connective-muscular, type I), which contain blood and lymphatic vessels, as well as lymphatic cysternas, and single-layered, formed only by a smooth muscular system (type II). Intranodal lymphatic sinuses are subdivided into subcapsular, peritrabecular and medullary sinuses. The subcapsular sinuses and sinuses related to trabeculae of type I and their branching is the most developed. At the tissue level, the lymph node parenchyma has a clearly manifested lobular structure. Lymphoid lobules in the lymph node parenchyma are positioned diffusely (mosaically) and consist of four main cellular zones: transit and cell-cell interaction (analogous to the cortical plateau), clonal proliferation of T- and, respectively, B-lymphocytes (deep cortex units, lymphatic nodules), accumulation of plasmocytes and synthesis of antibodies (brain cords). The lymphoid lobes (compartments) of the lymph nodes parenchyma are bipolar, their tops formed by the zones of transit and cell-cell interaction, and also by the zones of proliferation of B lymphocytes, and the bases by a complex of brain cords (zone of accumulation of plasmocytes and synthesis of antibodies). The zone of T-lymphocytes proliferation is in intermediate position and underlies the subunits of the parenchyma. The tops of the lymphoid lobes are located along the sinuses of the trabeculae of type I and the bases along the sinuses of the trabeculae of type II, which form the efferent lymphatic vessels. The maximum relative capacity of all studied lymph nodes was typical for zones of plasmocyte accumulation and synthesis of antibodies (19–27%), the minimum capacity was typical for transit and cell-cell interaction zones (3–8%). The relative capacity of zones of clonal proliferation of T- and B-lymphocytes in most lymph nodes was 1.5–3.0 times less than that of the zone of plasmocyte accumulation and antibody formation and was, respectively, 8–16% and 9–18%. The study showed that the structure of the lymph nodes parenchyma of dromedaries is not absolutely unique. As in other mammal species, it is subdivided into specialized cell zones which are connected in lymphoid lobules. Specific features of parenchyma structure include: diffuse (mosaic) location of lymphoid lobules; absence of signs of regulated localization of lymphoid lobules relative to the capsule and the sinus bordering the nodes.